Analisis Stabilitas Kapal Pbl Conveyor - Budi Utomo (Politeknik Negeri Madura, 2018)
PBL conveyor is a barg vessel that has been modified with the addition of conveyor on the left side of the ship. the addition of this conveyor is used for ship loading and unloading activities. with the addition of conveyor on the left side of the tentukanya will result in changes in the calculation of ship stability. the purpose of this study is to calculate the ship after the conveyor added. The method used is to use numerical method using software help. Reference stability calculation using IMO (International Maritime Organization). 1993. Code A.749 (18) Ch 3 - design criteria applicable to all ships. After recalculation, the maximum GZ arm of the 30 Req (Deg), whereas the reference from IMO arm of GZ maximum is 25 Req (deg). For the safety of recommendation when doing the loading and unloading activity of the minimum minimum tank filler 80%.